THE WORK OF THE CHINESE WRITER WEI WEI (魏微) IN “NETWORK LITERATURE” (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
With the rapid development of computer and network technologies, the creation and distribution of literary works has made the transition from paper media to online media. Today, with the help of the Internet, you can find and read literature in any language in the world. Writers in different languages have been given the opportunity to market and publicize their works online. The era of Internet technology began in China, as well as in developing countries of the world. The trend of feminist thinking has contributed to the improvement of the social status of women. Women are trying to fight for their voice and learn a new meaning of gender equality. This search is also reflected in literary works. Among the works of women's online literature, a large share is occupied by short stories and novels depicting the romantic life of the city. These types of novels and short stories mainly describe various forms of women's struggle for survival in modern cities. The events and characters in it are taken from life and are usually very different from traditional literature.